Galaxy pairs in cosmological simulations: Effects of interactions on colours and chemical abundances - Perez, María Josefa (2006)
We perform a statistical analysis of galaxies in pairs with a Λ-CDM scenario by using the chemical GADGET-2 of Scannapieco et al. (2005, MNRAS, 364, 552) in order to study the effects of galaxy interactions on colours and metallicities. We find that galaxy-galaxy interactions can produce a bimodal colour distribution where galaxies with significant recent star formation activity contribute mainly to blue colours. In the simulations, the colours and the fractions of recently formed stars of galaxies in pairs depend on their environments more strongly than those of galaxies without close companions, suggesting that interactions play an important role in galaxy evolution. If the metallicity of the stellar populations is used as the chemical indicator, we find that the simulated galaxies determine luminosity-metallicity and stellar mass-metallicity relations that do not depend on the presence of a close companion. However, in the case of the luminosity-metallicity relation, at a given level of enrichment, we detect a systematic displacement of the relation to brighter magnitudes for active star forming systems. Regardless of relative distance and current level of star formation (SF) activity, galaxies in pairs have stellar populations with higher level of enrichment than galaxies without a close companion. In the case of the gas component, this is no longer valid for galaxies in pairs with passive star formation that only show an excess of metals for very close pair members, consequence of an important recent past star-formation activity. In agreement with observations, the signature of gas inflows driven by interactions can be also detected in the lower mean O/H abundances measured in the central regions of galaxies in pairs. Our results suggest that interactions play a significant role in the determination of colour and chemical properties of galaxies in hierarchical clustering scenarios, although SN energy feedback is needed to achieve a full agreement.